MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA CIBENING, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - ME, Azizah Mursyidah; Anwar, Miftakhul; Qodariah, Hijri Laelatul (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2023)
Islamic Banks are very important to pay attention to finance business capital development. One of the causes of not developing a business is a lack of business capital. Therefore, a community service program is needed through introduction that is able to support regional economic growth. Community service activities are carried out to provide knowledge and insight to the community regarding how to choose the right sharia-based financing products through collaboration with Islamic Banks Indonesia. This community service was carried out in Cibening Village, Pamijahan District, Bogor Regency.